Association of microRNAs with Types of Leaf Curvature in Brassica rapa - Ren, Wenqing; Wang, Han; Bai, Jinjuan; Wu, Feijie; He, Yuke (Frontiers in Plant Science, 2018)
Many vegetable crops of Brassica rapa are characterized by their typical types of leaf curvature. Leaf curvature in the right direction and to the proper degree is important for the yield and quality of green vegetable products, when cultivated under stress conditions. Recent research has unveiled some of the roles of miRNAs in Brassica crops such as how they regulate the timing of leafy head initiation and shape of the leafy head. However, the molecular mechanism underlying the variability in leaf curvature in B. rapa remains unclear. We tested the hypothesis that the leaf curvature of B. rapa is affected by miRNA levels. On the basis of leaf phenotyping, 56 B. rapa accessions were classified into five leaf curvature types, some of which were comparable to miRNA mutants of Arabidopsis thaliana in phenotype. Higher levels of miR166 and miR319a expression were associated with downward curvature and wavy margins, respectively. Overexpression of the Brp-MIR166g-1 gene caused rosette leaves to change from flat to downward curving and folding leaves to change from upward curving to flat, leading to the decrease in the number of incurved leaves and size of the leafy head. Our results reveal that miRNAs affect the types of leaf curvature in B. rapa. These findings provide insight into the relationship between miRNAs and variation in leaf curvature.